The Efforts of Tahfidz Quran Teachers in Developing Arabic Language Communications for SD/MI Levels - Nasution, Mutiara Mardiah; Yusnaldi, Eka (Universitas Pahlawan Tuanku Tambusai, 2022)
This study aims to describe the efforts of tahfidz Quran teachers in the development of Arabic communication for elementary/MI students. The research approach is qualitative with a case study method at Maskanul Huffadz Al-Lu'lu, having its address at Bakaran Batu Village, Batang Kuis District. The data collection of this research was carried out in a structured manner using observation, interview, and documentation techniques. The results of this study found that the efforts made by tahfidz Quran teachers in developing Arabic-language communication for students (santri) were carried out using the muhaddatsah (dialogue) method. The dialogue in question is Arabic conversation between teachers and students, as well as between students and students. Thus, fluency and fluency in language make it easier for students to understand the meaning and focus of conversation using Arabic.